Night train - Trzaskowski, Andrzej 1933-1998 (Second Run, 2012)
"Ein Arzt, dem die operative Rettung einer Selbstmörderin mißlang, und eine Frau, die einer erloschenen Liebe zu entfliehen versucht, teilen durch Zufall ein Schlafwagenabteil. Eine psychologische Verhaltensstudie mit pessimistischen Untertönen. Vorzüglich inszeniert und gespielt." [filmdienst.de]
Original: Polen 1959
Special features: presented from a superb new high-definition restoration of the film, supervised by the film's cinematographer Jan Laskowski ; "About 'Night train'": an extract from a documentary on Jerzy Kawalerowicz ; new and improved english subtitle translation ; 16-page booklet featuring a new essay by writer and film historian Michael Brooke ; optimal quality dual-layer disc
Bildformat 1.33:1
Keywords: Film; DVD-Video